A Feasibility study on HEALWELL EMG PC100 - Alejandro, Cherrie May (College of Engineering, 1999)
HEALWELL EMG PC100, a product of Healwell Medical Equipment, Inc. is a PC-based electromyograph (EMG). it is a biomedical device which amplifies the electrical impulses emitted by the nerves and muscles and displays it for medical interpretation. It is used in the diagnosis and treatment of diseases of the muscles, spinal cord, motor neurons and neuromuscular joints. HEALWELL EMG PC100 was developed by the Electrical and Electronics Department of the College of Engineering, UP Diliman. It is the first locally manufactured EMG in the Philippines. It is designed as a cost effective alternative to the current imported EMG models available in the market and used in hospitals today. The whole EMG package consists of the following: (1) EMG unit which handles the amplification of electrical impulses, conversion of the signals to the useful information and the stimulation of the patient; (2) EMG software which comes with the CD installer and is responsible for initializing the test conditions and storing, processing and generating reports; (3) the USB connections which connects the EMG unit to the personal computer, laptop or notebook and enable it to access the EMG software; and (4) probes which are connected to the patient for electrical stimulation . The product is able to perform tests like electromyogram, nerve conduction, evoked potentials and repetitive nerve stimulation. The product is portable, easy to install and easy to upgrade. IT features lesser external notches. IT provides electrical isolation for maximum patient safety. IT uses the flexible and popular USB interface and it features a DSP/microcontroller based design. Based on the market, technical, organizational, financial and social profitability analysis of HEALWELL EMG PC100, for study period 2000 to 2004, the product shows feasibility in all aspects. Thus business venture promises high profitability. The market analysis shows that the target market for the product includes secondary and tertiary hospitals in the Philippines without EMG. This is based on a segmentation according to the kind of institution, categorization of hospitals and ownership of the EMG. furthermore, the market analysis shows increasing trend for demand and supply of the product however a great part of the demand is not met by supply. For the years 2000 to 2004, HEALWELL Medical Equipment, Inc. increases its market share every year with the highest market share occurring in 2004. for the first five years of the life of the project, it plans to sell a total of 163 EMG units starting with 8 units in the first year and increasing its sales volume to 49 units in the fifth year. The company plans to use distributors in selling the product. The distributors get a 15% share based on the selling price of Php650,000/unit. Marketing for the product includes the use of product brochures, calling cards, product launching, ad publication in medical journals, and dependable customer service. The technical analysis of the product shows that the technology to produce the product is available and thus production of the product is possible. The whole production process would be done manually. This would consist mainly of assemble and testing of the parts. Most of the parts would be bought and would not be manufactured. The production plan for the years 2000-2004 is to produce one-fourth of the sales volume at the start of every quarter. For production,, an engineer and technician would be employed. The total project cost which includes the working capital for 3 months operation is Php1,801,254.89. This amount of money is needed to start the business. The organizational analysis of the company shows that HEALWELL Medical Equipment, Inc. would be established as a corporation. It would be subject to the laws and requirements governing a corporation. The organizational structure of the key personnel of the company shows that the general manager at the top followed by the chief engineer. under the chief engineer are the engineer and the technician. The financial analysis of the business shows a strong financial position for the company. Based on the income statement of the first five years of the business, an increase in net income is seen. The cash flow statement also shows positive cash balances at the end of each year for the first five years. The balance sheet shows increasing assets and retained earnings for the company. Moreover, the net present value (NPV) amounting to Php15,021,990.02 is greater zero and the internal rate of return (IRR) of the business is greater than the 30% MARR (minimum attractive rate of return). The payback period is 1.07 years. The results of the NPV, IRR, and payback period show that the project is highly acceptable. Finally, the social profitability analysis shows a significant number of benefits identified in the project. There is improvement in the standard of living, lowering of prices from importation to local production, utilization of local resources, increase in the number of hospital with EMGs. Local and national government would benefit from the municipal, import, corporate and personal income taxes. Resulting from this product innovations, national science as a whole will also be accorded honor and prestige as well as motivation for other inventors and innovators. A disbenefit of the project is its contribution to the country's trade deficit resulting from the importation of some raw materials which are not available locally. The benefit-cost ratio of 5.155 of the project indicates that the benefits outweighs the costs.